Design and fabrication of the blow mold component - Mohd Azuan, Abu Shah (2007)
This report is an outcome of the work carried out in doing and completing final year project, Design and fabrication ofthe blow mold component. Objectives of this project is to design and running a simulation of blow mold for water bottle with aided of Master CAM commercial package as well as to gain the knowledge on fabricating process of the blow mold using CNC milling machine. Material that have been used is aluminum, which is the same material used for the real industrial mold. Overall, this project was run based on three main steps; design using Solid Work, running a simulation on Master CAM and fabricate using CNC Milling Machine. As for the research process, it starts off with an introduction on blow mold, which includes mold material and design; and a review on the software package being used which is a Master CAM commercial package. Then a further introduction focused on details about CNC Milling Machine. The method of conducting a Design and Simulation is presented; step by step. This is followed by a specific description of material used and machining process. Finally, the actual results of the simulations and the bottle models are presented and discussed. A conclusion on project simulation and accuracy of the models used, as well as the problem that occur during completing it, is then presented.